Prevalence of otitis externa in stray cats in northern Italy. Issue 6 (June 2014) - Perego, Roberta; Proverbio, Daniela; Bagnagatti De Giorgi, Giada; Della Pepa, Alessandra; Spada, Eva
Feline otitis externa is a dermatological disorder that has not been evaluated much in stray cats. One hundred and eighty-seven stray cats were randomly selected during a trap–neuter–release programme to investigate the prevalence of otitis externa in stray cat colonies in northern Italy. Swabs for cytological examination were obtained from the external ear canal of each cat. A direct otoscopic assessment of the external ear canal was made in 86/187 cats. Cytological evidence of otitis externa was present in 55.1% of cats. The influence on otitis of age, gender, habitat and season of sampling was tested, but no risk factors were found. Otodectes cynotis (as a sole agent or in combination) was the primary cause of otitis in 53.3% of cats. Cocci and rods, either alone or in combination with other agents, were perpetuating factors in 71.8% and 29.1% of cats, respectively. Pregnancy status was a risk factor for otitis caused by coccal infections. Malassezia species, alone or in combination, was the perpetuating factor in 50.5% of cats with otitis. Urban habitat and winter season were risk factors for otitis associated with Malassezia species. Demodex cati was identified as an incidental finding in two cats. There was good agreement between otoscopy and cytology with regard to the diagnosis of otitis externa. The results of this study show a high prevalence of otitis externa in stray colony cats and provide information on causal factors for feline otitis externa.